Global Research Trends on the Utilization of Black Soldier Fly in Ruminant Nutrition (2004–2025): A Scopus-Based Bibliometric Analysis - Mhd Adanan Purba; Randi Mulianda; Rita Rosmala Dewi; Reno Martha; Novia Qomariyah; Rakhmad Perkasa Harahap; Karina Mia Berutu; Zein Ahmad Baihaqi; Indra Joni (Faculty of Animal Science, Jenderal Soedirman University in associate with the Animal Scientist Society of Indonesia (ISPI) and the Indonesian Association of Nutrition and Feed Science (AINI), 2026)
The growing demand for sustainable protein sources in ruminant production systems has intensified scientific interest in black soldier fly larvae (BSFL; Hermetia illucens L.) as an alternative feed ingredient. This study presents a comprehensive bibliometric analysis of global scientific publications on the use of BSFL in ruminant nutrition. Bibliographic data were retrieved from the Scopus database for the period 2004–2025 and analysed using established bibliometric tools to assess publication trends, citation patterns, collaboration networks, source concentration, and thematic evolution. A total of 194 peer-reviewed documents were identified, published across 115 sources by 903 authors, with a mean of 6.0 authors per article and 36.08% international co-authorship. Publication output increased markedly over the past decade, indicating that BSFL research has emerged as a rapidly developing and multidisciplinary field. Thematic analysis revealed a clear transition from early studies centred on basic biology and waste bioconversion toward applied research addressing ruminant nutrition, feed efficiency, and sustainability. Source analysis further showed that although insect- and feed-specific journals dominate publication volume, environmental journals attract disproportionately higher citation intensity, suggesting that the field remains conceptually anchored in circular-economy frameworks rather than fully integrated into mainstream animal nutrition science.